Essays on the future of agricultural productivity and meat demand: evidence in China and the United States - Tian, Yongxia (My University, 2026)
Since the introduction of hybrid maize in the 1930s, U.S. corn yields have increased at the rate of 1.8 bu/acre/year. Concomitantly, corn plant populations (plants/acre) more than doubled. Thus, the increase in yields has primarily taken the form of more plants/acre, rather than more yield/plant. But this raises some important questions: What is the upper limit for plant populations, have we already reached it, and what does this imply for future corn productivity? This study investigates these questions using county-level panel data on US corn yields, plant populations, and weather variables from 1960-2023. While plant population changes have been arguably the most crucial mechanism for yield growth, this study shows we may be approaching an upper limit. U.S mean plant populations have not increased, on average, since 2015, and yield projections based on a slowdown in plant population growth suggest a major potential slowdown in yield growth. This second article examines meat consumption behavior and its dynamics across four meat categories (pork, beef, poultry and lamb) in urban and rural China. We adopt an extended dynamic demand system that incorporates both habit formation and pre-committed effects and estimates the model using provincial level data from 30 provinces during the period 2015 to 2022. Results from the dynamic demand system show that while all four meat categories are habitual, beef is the most habitual meat in the urban and rural consumption groups, however, rural consumers display a higher degree of habit formation in their diets. Additionally, we provide evidence that factors beyond price and expenditure play a significant role in shaping both urban and rural consumer demand responses for pork and poultry. Using long-term elasticities, we predict changes in budget shares for meat consumption over the next decade, indicating that beef and poultry are likely to take a larger portion of future meat expenditure. This third paper uses agricultural data from 31 Chinese provinces during the 2000–2022 period to examine whether China’s Five-Year Plans (FYPs) induced or inhibited differential productivity across provinces. Productivity performance and heterogeneity are first assessed using a Malmquist productivity index. Convergence tests confirmed “catch-up” effects, where regions with lower productivity growth gradually move towards a unified steady state equilibrium state, but no clear convergence was observed nationally or regionally, except in the western provinces. Econometric analysis shows that the twelfth FYP reduced differential provincial total factor productivity (TFP), while this effect was not significantly significant in the thirteenth and fourteenth FYPs. Budgetary and financial policies appear to mitigate this divergence, whereas education policies may have induced disparities due to labor outflows and rural aging. This study has significant policy implications for the formulation and evaluation of future FYPs. Specifically, central government strategies should be closely coordinated with provincial initiatives, progress should be monitored at each stage, and plans should be continuously adjusted to ensure effective implementation. Future research could extend this analysis by incorporating survey data on the performance and evaluation of FYPs at each stage.
Keywords: Corn yield; Corn plant population; Yield prediction; Dynamic AIDS; China's meat demand; Consumer behavior